Plasma transfusion in liver transplantation: a randomized, double‐blind, multicenter clinical comparison of three virally secured plasmas. Issue 6 (24th September 2012) - Bartelmaos, Tonine; Chabanel, Anne; Léger, Julie; Villalon, Loïc; Gillon, Marie Christine; Rouget, Claude; Gomola, Alexandra; Denninger, Marie Hélène; Tardivel, René; Naegelen, Christian; Courtois, Françoise; Bardiaux, Laurent; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND: The clinical equivalence of plasma treated to reduce pathogen transmission and untreated plasma has not been extensively studied. A clinical trial was conducted in liver transplant recipients to compare the efficacy of three plasmas. STUDY DESIGN AND METHODS: A randomized, equivalence, blinded trial was performed in four French liver transplantation centers. The three studied (fresh‐frozen) plasmas were quarantine (Q‐FFP), methylene blue (MB‐FFP), and solvent/detergent (S/D‐FFP) plasmas. The primary outcome was the volume of plasma transfused during transplantation. Secondary outcomes included intraoperative blood loss, hemostasis variables corrections, and adverse events. RESULTS: One‐hundred patients were randomly assigned in the MB‐FFP, 96 in the S/D‐FFP, and 97 in the Q‐FFP groups, respectively. The median volumes of plasma transfused were 2254, 1905, and 1798 mL with MB‐FFP, S/D‐FFP, and Q‐FFP, respectively. The three plasmas were not equivalent. MB‐FFP was not equivalent to the two other plasmas, but S/D‐FFP and Q‐FFP were equivalent. The median numbers of transfused plasma units were 10, 10, and 8 units with MB‐FFP, S/D‐FFP, and Q‐FFP, respectively. Adjustment on bleeding risk factors diminished the difference between groups: the excess plasma volume transfused with MB‐FFP compared to Q‐FFP was reduced from 24% to 14%. Blood loss and coagulation factors corrections were not significantly different between the three arms. CONCLUSION: Compared to both Q‐FFP and S/D‐FFP, use of MB‐FFP was associated with a moderate increase in volume transfused, partly explained by a difference in unit volume and bleeding risk factors. Q‐FFP was associated with fewer units transfused than either S/D‐FFP or MB‐FFP.